Move, Learn, and Stay Healthy: Edukasi Olahraga untuk Masyarakat Sehat - Alimin Hamzah; Nurul Ichsania; Nurul Ilmi; Ani Asram (Universitas Cokroaminoto Palopo, 2026)
The increasing prevalence of non-communicable diseases and low levels of physical activity remain major challenges in health promotion and disease prevention efforts. Limited public understanding regarding the relationship between exercise and body metabolism also contributes to low awareness in maintaining a healthy lifestyle consistently. This community service program aimed to improve sports health literacy and basic biochemical understanding through health education among athlete communities at the Faculty of Sports and Health Sciences (FIKK) Universitas Negeri Makassar. The program applied a community-based participatory health education approach integrating interactive health coaching, group discussions, simple simulations, light physical activity practices, and reflective participation methods. A total of 36 athletes participated in the activity. Evaluation was conducted without using pre-test and post-test methods, but through reflective participatory evaluation, participant engagement observation, and direct feedback sessions. The results showed increased participant understanding regarding the importance of physical activity, energy metabolism, hydration, body recovery, and the relationship between exercise and biochemical processes in the body. Participants also demonstrated active engagement and enthusiasm throughout the program. This activity positively contributed to improving healthy lifestyle awareness and participants’ commitment to sustainable physical activity. Therefore, participatory sports health education can serve as an effective strategy to support health promotion and improve quality of life, particularly among young athlete communities.